ANALISIS FAKTOR YANG MEMENGARUHI PROFITABILITAS UMKM DI KECAMATAN KALIMANAH PURBALINGGA - Dianningsih; Kristianto, Giovanny (Fakultas Ekonomi, Bisnis dan Humaniora, 2023)
Today, MSMEs are increasingly mushrooming and increasing, as indicated by the gross domestic income of a region increasing significantly. Success in the performance of an MSME is marked by an increase in the profitability of the MSME business. Management that regulates the operations of MSMEs has a role in making economic decisions for business continuity. There are several factors that influence the profitability of MSMEs, namely length of business, digital marketing, business location and information technology which are independent variables in this research. This research was conducted in Kalimanah District, Purbalingga Regency with the sample being MSME actors in the culinary sector. The research results show that from the questionnaire distributed to 190 respondents, it can be concluded that partially, the length of business does not affect business profitability. However, digital marketing, business location and information technology partially have a significant and positive influence on the profitability of MSME businesses. Simultaneously, length of business, digital marketing, business location and information technology have a significant and positive influence.